Patočka i Masaryk - Zumr, Josef (Folia Philosophica, 2018)
The aim of the paper is to analyse relation between Jan Patočka and Tomáš G.Masaryk. The former was referring to the latter’s concepts throughout his work, inmost  cases  from  the  perspective  of  Edmund  Husserl’s  phenomenology.  According  toPatočka, both in Masaryk and Husserl the most important symptom of crisis is thepositivist  hypostising  of  the  scientific  method  and  the  loss  of  religion.  The  commonstarting  point  of  both  theories  was  the  thesis  according  to  which  Europe  is  goingthrough  a  spiritual  crisis  which  arises  from  subjectivism.  The  difference  betweenthem,  however,  was  in  the  concepts  of  the  ways  to  resolve  the  crisis.  According  toMasaryk, the solution is to be found in restoration of religion, whereas Husserl seesit in transcendental phenomenology. Patočka was wrong when he stressed how muchout of date were Masaryk’s views. For they might be taken as topical in their moraland  religious  aspects,  value  of  which  was  proved  during  the  hard  times  for  Czechand Slovak nations.